Time patterns in online survey completion and offline psychological symptoms among college students in China - Liu, Yiyang; Xu, Shuang; Yang, Peiyue; Feng, Haolou; Wu, Shaoshuai; Yin, Xiaoping; Zhang, Guowei; Lu, Qi; Dong, Zhichen; Li, Shunfei; Chen, Hongguang (Frontiers in Public Health, 2024)
Background Online psychological surveys allow for swift data collection among college students, thus providing a foundation for psychological interventions, particularly during emergent public health events. However, the association between online survey completion behaviors and offline psychological symptoms has yet to be explored. Methods A large-scale web-based survey was conducted from December 31, 2022, to January 7, 2023, involving 22,624 participants. Psychological symptoms were assessed using standardized measures, while the time taken to complete the survey and the time of completion were recorded by the online survey platform. Results As the time duration increased, the prevalence of anxiety, depression, insomnia, and PTSD also increased significantly (Pfor trend < 0.001). The highest odds ratios were observed in the longer duration group. Only a longer duration was significantly associated with PTSD. The time period for completing the questionnaire from 7 p.m. to 10 p.m. was found to be significantly linked with anxiety symptoms and depression symptoms. Conversely, completing the questionnaire at other times was specifically associated with anxiety symptoms and insomnia symptoms. The prolonged duration needed to complete the questionnaire was more closely related to the comorbidity of anxiety, depression, and insomnia than to the comorbidity of those symptoms with PTSD. When questionnaires were completed during other times, specifically referring to the late-night and early morning hours, individuals were more likely to exhibit comorbid symptoms of insomnia. Conclusion The study identified the specific associations between time durations, time points for completing online survey, and psychological symptoms/comorbidity among college students. Further exploration of their causal relationships and the underlying mechanisms is warranted.